SUFISM AND MENTAL HEALTH (PENDIDIKAN TASAWUF DAN KESEHATAN MENTAL) - Sukarta (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2022)
This article is a result of research that describes where Sufism education can actually affect human mental health. This study uses a qualitative method using a tasawuf approach in understanding the object of the verses of the Qur’an related to tasawuf and the relationship between humans and God. Therefore, in this article, researchers explore further mental health and its relationship to God Almighty. So that in its goal, researchers can easily find out the implications for physical and spiritual balance in every human being.